IMPLIKASI FILSAFAT PENDIDIKAN ESENSIALISME DALAM PENDIDIKAN KARAKTER - Mukmin, Mukmin (Fakultas Agama Islam Universitas Kutai Kartanegara Tenggarong, 2022)
The doctrine of essentialism, one of the traditional schools of educational philosophy, states that values in education must be based on distinct and enduring values in order for education in a country to remain stable and purposeful. The purpose of this research is to examine the implications of the philosophy of essentialism education in character education. The research method used is a literature study based on content analysis. The results show that the purpose of essentialism education philosophy is to improve the character of society through the cultural heritage that still exists, so that students in the future can contribute to the improvement of people's lives in the face of changing times that can erode students' morals. In addition, the philosophy of essentialism aims to create a happy person in this world and the hereafter by instilling virtuous values (morals, manners, and morals) to students because schools, teachers, and students are the key to building a developed nation and play an important role in character development in the school environment and society. This article seeks to conceptualize the goal of essentialism, which is to form a happy person in this world and the hereafter, through character development and the importance of the role of teachers in the formation of student character in schools and society.